Pengaruh Debt To Total Asset Ratio Terhadap Return On Equity dan Manfaat Ekonomi Anggota: (Studi Kasus pada Koperasi Karyawan Bank BJB “ZIEBAR” Kota Bandung) - Eka Setiajatnika; Muhamad Ardi Nupi, Hasyim; Risma, Oktavira (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2020)
One of the important decisions faced by cooperatives is the decision on capital structure, namely financialdecisions relating to the composition of debt. How much the use of debt can improve services in theCooperative business unit and how much the use of debt can produce optimal profits. The method used inthis research is the case study method, which is a research method by collecting data and direct observationof the object under study in order to find out and understand the solution of problems in the BJB BankEmployees Cooperative